Yield, accumulation and distribution of biomass in sunflower depending on salinity and nitrogen - Escalente-Estrada, José Alberto Salvador; Aguilar Carpio, Cid; Escalante-Estrada, Yolanda Isabel (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of the study was to determine the effect of nitrogen in sunflower under saline soils, on the variable, days to phenological stages, total biomass, harvest index, yield, grain size, number of grains, chapter area, number of grains per chapter, accumulation, and distribution of dry matter. The cultivar Victoria Mejorada was planted in soils with different levels of salinity (2 and 7 dS m−1) and nitrogen (0 and 100 kg ha−1). Salinity and nitrogen do not affect phenological phases, grain size, harvest rate and dry matter distribution. The biomass, yield, number of grains, area of the chapter, number of grains per chapter and the accumulation of dry matter in each organ of the plant was reduced by the high salinity of the soil, however, the application of 100 kg ha−1 of nitrogen generated a greater accumulation of dry matter and yield in sunflower.